Integrasi Sistem Reward dan Penilaian Kinerja Berbasis KPI dalam Mendukung Knowledge Management pada Layanan Pelanggan Digital - Muhammad Edwinsyah; Fairuz Fernanda Hermawan; Ledi Dinayatullah; Muharman Lubis (STIKOM Tunas Bangsa Pematangsiantar, 2025)
In the digital service era, the role of Knowledge Management (KM) becomes increasingly critical in ensuring efficient, responsive, and high-quality customer interactions. However, the effectiveness of KM implementation is not only determined by technological infrastructure, but also by the motivation and active participation of service agents. This study examines the integration of reward systems and Key Performance Indicator (KPI)-based performance appraisal in supporting KM practices within digital customer service environments. Using a Systematic Literature Review (SLR) method and a reflective case study of the live chat service unit of a leading Indonesian e-commerce company (Bukalapak), this research reveals how reward mechanisms and KPI structures influence knowledge sharing behaviors, agent performance, and service quality. The findings indicate that hybrid KPI systems combining quantitative metrics (such as response time and CSAT) and qualitative assessments (such as communication quality) alongside tiered reward schemes, significantly enhance agent engagement and knowledge utilization. Additionally, continuous feedback from the Quality Assurance team strengthens organizational learning and service innovation. This study offers theoretical and practical contributions in designing integrated strategies to reinforce KM through performance measurement and motivation systems in digital service sectors.